2018
DOI: 10.1111/jch.13386
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorothiazide vs chlorthalidone, indapamide, and potassium‐sparing/hydrochlorothiazide diuretics for reducing left ventricular hypertrophy: A systematic review and meta‐analysis

Abstract: Left ventricular hypertrophy develops in 36%‐41% of hypertensive patients and independently predicts cardiovascular events and total mortality. Moreover, drug‐induced reduction in left ventricular mass (LVM) correlates with improved prognosis. The optimal thiazide‐type diuretic for reducing LVM is unknown. Evidence regarding potency, cardiovascular events, sodium, and potassium suggested the hypothesis that “CHIP” diuretics (CHlorthalidone, Indapamide, and Potassium‐sparing diuretic/hydrochlorothiazide [PSD/HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
1
26
0
1
Order By: Relevance
“…However, the recent meta‐analysis showed superiority of CHIP diuretics over hydrochlorothiazide and even renin‐angiotensin system inhibitors in the regression of LVH . The present study confirmed that CHIP diuretics surpassed hydrochlorothiazide in reducing LVM …”
supporting
confidence: 82%
See 4 more Smart Citations
“…However, the recent meta‐analysis showed superiority of CHIP diuretics over hydrochlorothiazide and even renin‐angiotensin system inhibitors in the regression of LVH . The present study confirmed that CHIP diuretics surpassed hydrochlorothiazide in reducing LVM …”
supporting
confidence: 82%
“…The authors showed that a 1% decline in systolic blood pressure predicted a 1% decline in LV mass (LVM). Diastolic blood pressure decline also predicted LVM reduction; however, after adjustment for systolic blood pressure, diastolic blood pressure lost its predictive value as a predictor of LVM . The present meta‐analysis revealed that Chlorthalidone, indapamide, and potassium‐sparing diuretic (CHIP), alone or combined, were superior to hydrochlorothiazide for reducing LVM .…”
mentioning
confidence: 66%
See 3 more Smart Citations